SERVIVE QUALITY ON EDUCATION INSTITUTION: SATISFACTION INDEX AND IPA (CASE STUDY ON ACCOUNTING DEPARTMENT OF STATE POLYTECHNIC OF MALANG) - ., Sumiadji; Handoyo, Futuh; Setiati, Fita (International Journal of Social Science and Business, 2019)
The purpose of this study was to determine the level of student satisfaction towards the quality of service provided by the Accounting Department, State Polytechnic of Malang (Polinema), by comparing the actual service delivered by the institution to the one expected by the students. Respondents as samples were determined proportionally for each study program and class of as many as 100 students. The questionnaire was randomly given to respondents to obtain a response to service quality consisting of 5 (five) dimensions, namely tangible, reliability, responsiveness, assurance and empathy. Data analysis was descriptive analysis prosiding from descriping the data in term of the mean and frequency, and than measuring student satisfaction index and ending up with determining the service quality using importance-performance analysis (IPA). The results showed that  most respondents were DIV Management Accounting study program students, of whom the majority were female. The frequency of the students response for the quality of the received service fell into the catagory of very satisfying, which means that, in general, the quality of service received by students was very satisfying. There were found two dimensions in quadrant A where two forms of service quality must be improved immediately, four dimensions in quadrant B where six forms of service quality must be maintained, and all dimensions in quadrant D where eight forms of service quality in the short term may be ignored.